Avaliação da resistência de união de diferentes cimentos resinosos a dentina radicular - Barros, Dalila Viviane (2011)
The aim of this study was to evaluate the bond strength to dentin of three resin cements used for cementation of glass fiber posts in three different root depths (cervical thirds, middle and apical). We selected 30 bovine teeth were endodontically treated and prepared to conduct cementing glass fiber posts. Resin cements were used: Allcem-FGM Dental Products LTD, resin cement RelyX ARC dual-3M ESPE, Self-Adhesive Resin Cement RelyX U100 Universal, 3M ESPE. The samples were cross-sectioned into six slices resulting in two discs 1 mm thick by region: cervical thirds (c1 and c2), medium (M1 and M2) and apical (A1 and A2). The slices were tested with micropush out on a machine EMIC DL 2000, containing a load cell of 50kgf under 0.5 mm / minute. The data were subjected to One-way ANOVA (cement) with split-plot (third root) are using the Tukey test (α <0.05) for comparison between groups. The results showed that the bond strength was influenced by cement, and in the cervical region, the cement RelyX Arc showed the highest bond strength, showing no statistical difference when compared with the the All hundred and statistically different when compared with the RelyX U100.A bond strength was also influenced by root third (p = 0.001) and the third cervical (p = 0.001) and medium (p = 0.015) showed higher bond strength when compared with the apical third. The interaction of cement and root third did not influence the results of bond strength (p = 0.076).